BRIEF RESULTS OF THE WEATHER ANALYSIS DURING THE OPERATION OF J.A.R.E. III, 1958-59 - Yushiro KUGA (National Institute of Polar Research, 1962)
1. Introduction J.A.R.E. III had to perform the operation to reopen Syowa Base which had been left unoccupied since Feb. 1958. According to the unfavourable ice condition in the vicinity of Lutzow-Holm Bay, the operation was forced to rely mainly upon the air-transportation, which is seriously affected by meteorological condition. Thus, the weather analysis and forecast became most important to gain success in the operation. The works were carried out by three meteorologists who were on board the expedition ship "SOYA". This paper brief by reports the results of the weather analysis for the area limitted between long. 40°W and 80°E. 2. General features of the synoptic pattern and the weather In early summer, from late December to middle January, the Antarctic continental anticyclone had retired to south, and the stationary front between the continental anticyclone and subtropical anticyclone was apt to be formed along the Antarctic coast. Under such a pattern, the "SOYA", hanging around Lutzow-Holm Bay, experienced unstable weather with variable wind, much lower cloud, and poor visibility. Sometimes she met moderate storm caused by the approach of developed cyclone. The transport operation, therefore, made little progress though every opportunity of short intermittent fine weather was utilized to enforce the air transportation. In late summer, the continental anticyclone became strengthened controlling over Lutzow-Holm Bay, and the weather both at the base and at the ship site was generally stable. The transport operation was performed during the succeeding fair weather from 1st to 4th February. 3. Cyclones The "SOYA" encountered three cyclones during the period from Jan. 2 to Feb. 11. Their trajectories are shown in Fig. 3, in which we can notice the retrogressive motion of two cyclones in the area south of lat. 60°S. This was caused by the existence of the superior high pressure ridge over Enderby Land, which prevented the cyclones to move east, associated with the general pattern of meridional circulation. ...